Imitation Equilibrium - Reinhard Selten; Axel Ostmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
The paper presents the concept of an "imitation equilibrium" and explores it in the context of some simple oligopoly models. The concept applies to normal form games enriched by a "reference structure" specifying a "reference group" for every player. The reference group is a set of other players, whom the player may consider to imitate. Some of these players may not be suitable for imitation for various reasons. Only one of the most successful of the remaining members of the reference group is imitated. Imitation is the adoption of the imitated player's strategy. Imitation equilibrium does not only mean absence of imitation opportunities but also stability against exploratory deviations of "success leaders", i. e. players most successful in their reference groups. Exploration declenches a process of imitation which either leads back to imitation equilibrium directly or by a "return path" after an unsuccessful deviation. The imitation equilibrium concept is motivated by the experimental literature which suggests that under appropriate conditions imitation of the most successful relevant other is an important behavioral force. The concept may be useful for the evaluation of experimental data and for planning of future experiments.
Keywords: C72; C91; C92; L13; 330; Imitation equilibrium; oligopoly; normal form games; experimental economics